The Use of Fuzzy Logic Methods to Optimize the Selection of Suppliers of the Enterprise - Murodian, L. O.; Kuchkova, O. V.; Chupryna, N. M.; Dotsenko, G. Ye.; Zhuravel, V. V.; Naumenko, N. Yu.; Sverdlikovska, O. S. (Science and Transport Progress, 2023)
Purpose. The current state of Ukraine’s economy dictates the requirements for optimizing the selection of a reliable supplier to ensure the stable operation of the enterprise. Therefore, the authors believe that one of the main conditions for the company’s activity is the improvement of logistics links. The main purpose of the study is to optimize the selection of suppliers of raw materials and supplies based on a logistics approach. Methodology. The article analyzes the performance indicators of suppliers of raw materials in the meat processing industry of Ukraine. The methodology for building an integral indicator of supplier competitiveness is presented. The modeling of the integral indicator of assessing the competitiveness of a raw material supplier using a fuzzy logic approach is carried out. The study was carried out using the methods of analysis and synthesis to determine the criteria and parameters for selecting a supplier of raw materials in order to organize the movement of material flows of the enterprise. Findings. The study found that the search for a new supplier of raw materials and supplies requires strict adherence to the selection algorithm. One of the elements of the algorithm is a study of the supplier market, which should be carried out using competitiveness indicators. The article assesses the competitiveness of pork and chicken suppliers in the Ukrainian market. The list of optimal suppliers for the uninterrupted supply of raw materials to meat processing enterprises is determined. Originality. The paper proposes a methodological approach to a more detailed analysis of raw material suppliers to enterprises, which allows applying elements of fuzzy logic to optimize the supplier selection process, unify diverse performance indicators, and compare the competitiveness of suppliers both within Ukraine and abroad. Practical value. The article proposes a model procedure for assessing the level of competitiveness of optimal suppliers of raw materials and supplies. The basis is the model of an integral indicator of competitiveness, the components of which are aggregate indicators. The use of fuzzy logic methods made it possible to formalize the obtained diverse indicators of activity of suppliers of raw materials and systematize them on a single scale. This made the supplier assessment model universal and expanded the possibilities of its use for practical purposes.